If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(w + 4) = 3(w + 4) + 7 Reorder the terms: -4(4 + w) = 3(w + 4) + 7 (4 * -4 + w * -4) = 3(w + 4) + 7 (-16 + -4w) = 3(w + 4) + 7 Reorder the terms: -16 + -4w = 3(4 + w) + 7 -16 + -4w = (4 * 3 + w * 3) + 7 -16 + -4w = (12 + 3w) + 7 Reorder the terms: -16 + -4w = 12 + 7 + 3w Combine like terms: 12 + 7 = 19 -16 + -4w = 19 + 3w Solving -16 + -4w = 19 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -16 + -4w + -3w = 19 + 3w + -3w Combine like terms: -4w + -3w = -7w -16 + -7w = 19 + 3w + -3w Combine like terms: 3w + -3w = 0 -16 + -7w = 19 + 0 -16 + -7w = 19 Add '16' to each side of the equation. -16 + 16 + -7w = 19 + 16 Combine like terms: -16 + 16 = 0 0 + -7w = 19 + 16 -7w = 19 + 16 Combine like terms: 19 + 16 = 35 -7w = 35 Divide each side by '-7'. w = -5 Simplifying w = -5
| 4(1,2x+3,7)-2,8=5,2x | | (x+1)(x-4)(2x-1)= | | 3x+3(5x-18)=108 | | -3(y+1)+7y=4(y+1)-5 | | -5+4x=7x-8 | | (x^3+5x-7)(x^2-7x-1)= | | -6(v+1)+8v=2(v-3) | | 4(x+1)-7=3(x-1)+x | | (x+3)(2x-1)=(x+3)(2-x) | | 3(v+2)+2v=7(v-1)+9 | | 10+3x=2x+5 | | 5m(m^2+5m-8)=0 | | 3(x+2)-x=2(x-1)+5 | | 5x+6=3x^2-9 | | -4.4q+1.3=-23.9-1.6q | | 3(w-2)-4w=2(w-9) | | -2(v+6)+6v=4(v-3) | | 2(x+2)+x=3(x-1)+6 | | .333333f-3=1 | | v=.333333bh | | x*x*x(3-4x)=4x(3-4x) | | x-1388=-15 | | x-745=-14 | | x(3-4x)=4x(3-4x) | | x-1450=734 | | .333p-.375p=3 | | x+235=-200 | | .333p-.375p=5 | | (8x^2-4x+6)(5x+5)= | | 1p-8p=5 | | -1/3=-3/2 | | (5x^2-2x-5)(3x+9)= |